Location and Structural Optimization of Transmission Tower in Hilly Region - V. K. Bansal; Pardeep Kumar; V. Suresh Kumar (International Journal of Scientific Research in Civil Engineering, 2022)
In the energy sector for infrastructure development, a major problem encountered is losses during transmission. In view of this, an important problem in energy transmission is to design an optimal route for the minimization of losses and structural configuration. The literature suggests the optimization for location (routing) and structure separately. To compare the efficiency of the components, both location and structural optimization have to be performed. In the present study, a detailed methodology for location and structural optimization of a transmission tower has been developed and performed. To validate the methodology a 132 kV single circuit angle tower transmission line tower was considered for location and structural optimization as a case study. To see the performance of the location and structural optimization, two types of conductors were chosen. Sag tension calculation was done for different temperatures: ice and wind cases. The transmission tower was configured by satisfying peak clearance, electrical clearance, and mid-span clearance using AutoCAD. Routing optimization of the transmission line was done using Dijkstra’s Algorithm-based Least Cost Path tool in ArcGIS. The criteria (slope, elevation, and restricted area) were ranked and weighted using Analytic Hierarchy Process (AHP). Tower spotting was done along the optimized route using sag temple through AutoCAD for both conductor types. The configured tower was modeled using AutoCAD, and analysis and design of the transmission tower were carried out in three dimensions using STAAD.Pro v8i software as per IS 800-2007. The size optimization method developed for transmission tower, both conductor types, gives directly the optimal section from user-provided steel table. The developed optimization method was compared with existing literature and the results were found satisfactory. By incorporating real cost factors in identifying the relative importance of location and structural aspects best configuration of the transmission line tower may be chosen using the developed methodology.